The representation of domestic violence in popular English-language cinema - Wheeler, Duncan (New Cinemas: Journal of Contemporary Film, 2009)
This article examines how domestic violence has been depicted in mainstream English-language cinema. I offer readings of Sleeping with the Enemy, Tina: What's Love Got to Do With It, Once Were Warriors, Nil By Mouth and Enough that examine both common and specific representational strategies. My analysis is grounded in theoretical approaches and heuristic tools more commonly found in feminist criticism than in film studies.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTM4Ni9uY2luLjcuMi4xNTUvMQ